THE LONG AND WINDING ROAD – BENCHMARKING TURKISH ACCESSION TO THE EUROPEAN UNION - Fifka, Matthias (Journal of European Economy, 2017)
In 2005, Turkey was officially welcomed as a member candidate for the European Union. The accession process, however, is the most difficult in the history of the EU. Aside from political and social controversies, the readiness of the Turkish economy is frequently doubted. The purpose of this paper is to examine the state of the Turkish economy and to compare it to the economies of Bulgaria and Romania at the time of their accession. The core analysis is based on the question whether the Turkish economy currently has a standard that is comparable to the economies of Bulgaria and Romania when their accession to the EU was agreed upon. If that was the case, the EU theoretically could not deny Turkish accession based on economic grounds.